The Planning of Business Processes in Undefined Condition of Oligopolistic Market - ALEXAKHIN A.V.; ZAYTSEV I.M.; SALA D.P. (Annals of the University of Petrosani: Economics, 2018)
Purpose – The article shows how in undefined condition in business processes. Methodology – Produced a review of the current state of the market secondary metallurgy of precious metals. The basic tenets of the theory of antagonistic games and show their application in an oligopolistic market recyclers of electronic scrap. It is shown that decision-making in the field of business process is advantageously carried out on the basis of market monitoring and behavior of other contracting parties, in particular, to their pricing decisions. Originality/value – The models, which can formalize the behavior of companies in an oligopolistic market and find a solution under conditions of uncertainty. The proposed rules non-cooperative interaction and competition rules are making management decisions on planning business processes, in particular, to ensure the natural resources of the enterprise. Findings – Improving the competitive strategy of raw materials procurement is possible through the use of guidelines defining their behavior in a competitive environment that include elements of game theory. Non-cooperative game models of interaction and competition can be used in the planning of business processes. Application management advice supply of raw materials necessary to make now can be used to implement the ability to manage the volumes supplied raw materials to attract more number of suppliers in the development of business processes, in particular in the field of planning, supply of raw materials on the basis of long-term relationships.